Minutes of the 2nd Meeting of BRAC University Governing Board (GB) - Governing Board, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 2nd Meeting of BRAC University Governing Board (GB) held at BRAC University on Monday, 9th July, 2001.